2022
DOI: 10.3390/sym14040769
|View full text |Cite
|
Sign up to set email alerts
|

Modern Method to Analyze the Heat Transfer in a Symmetric Metallic Beam with Hole

Abstract: The paper aims to use Modern Dimensional Analysis to study the heat transmission through a rectangular bar with a hole. The problem is very important for monitoring a structure, made of such bars, to protect it from fire. The original part of the work is represented by the application of this nonconventional method in the field of heat transfer in bars of rectangular-tubular section. During system heating, the properties of the material change dramatically at high temperatures, which can lead to the collapse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…As mentioned before in [64], the authors, based on the deduced ML in [57], performed a searching experimental investigation in order to validate the obtained ML for the case of the unprotected (without an intumescent paint layer) steel members.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned before in [64], the authors, based on the deduced ML in [57], performed a searching experimental investigation in order to validate the obtained ML for the case of the unprotected (without an intumescent paint layer) steel members.…”
Section: Methodsmentioning
confidence: 99%
“…Their applicability is strongly limited due to several shortcomings [35][36][37][38][39][40][41][42][43][44][45], analysed in detail by the authors in [1,[46][47][48][49][50][51][52][53][54][55][56][57][58]. Even CDA represents a relatively general approach; it also has several limits, including representing a relatively chaotic procedure in the identification of the dimensionless variables π j , j = 1, .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistics for this Special Issue related to published or rejected items were as follows [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]: 25 total submissions, 15 published papers (60%), and 10 rejected papers (40%). The geographical distribution of the authors of published papers is shown in Table 1, in which it can be seen that 50 authors are from seven different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%